Pulmonary dirofilariasis in a 59-year-old man - So, Tetsuya (Oxford University Press, 2014)
We present a case of a human pulmonary dirofilariasis in a 59-year-old man. At the medical examination, a chest computed tomography (CT) revealed a mass, measuring 18 × 15 mm in diameter, with an irregular margin on the bottom of the right lower lobe. We could not neglect the possibility of a primary lung cancer, and therefore, a lung partial resection was performed under video-assisted thoracoscopic surgery. The intra-operative pathological findings revealed inflammatory granuloma with coagulation necrosis and no malignant cells. The permanent pathological examination showed occlusion of the peripheral pulmonary artery by worms and formation of a necrotic mass surrounded by reactive inflammation and hemorrhage. Human pulmonary dirofilariasis is an extremely rare zoonotic infection, and sometimes it is difficult to distinguish it from a primary lung cancer on radiographic findings.